Efficacy of Huangqi Injection in the Treatment of Hypertensive Nephropathy: A Systematic Review and Meta-Analysis - Xu, ZhongChi; Qian, LiChao; Niu, RuGe; Yang, Ying; Liu, ChunLing; Lin, Xin (Frontiers in Medicine, 2022)
Background: Huangqi injection (HQI) is the extract of Astragalus membranaceus (Fisch.) Bunge, which is widely used in the treatment of a variety of diseases in China. It is supposed to be an important adjuvant therapy for hypertensive nephropathy. Objective: To evaluate the efficacy and safety of HQI combined with antihypertensive drugs in the treatment of hypertensive nephropathy. Materials and methods: We systematically searched China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wanfang Knowledge Service Platform (WanfangData), Chinese Biomedical Database (CBM), EMBASE, PubMed and Cochrane Library from their inception to April 23st, 2021. All studies were independently screened by two auditors according to the inclusion and exclusion criteria. Randomized controlled trials comparing HQI in combination with antihypertensive drugs versus antihypertensive drugs alone were extracted. Results: The meta-analysis included 15 studies involving 1483 participants.The effect of HQI combined with antihypertensive drugs is better than that of antihypertensive drugs alone in regulating hypertensive nephropathy for reducing 24-hour urinary total protein (24h UTP) [WMD = -0.29, 95% CI (-0.40, -0.18), P=0.000], microalbuminuria (mALB) [WMD = -17.04, 95% CI (-23.14, -10.94), P=0.000], serum creatinine (SCr) [WMD = -40.39, 95% CI (-70.39, -10.39), P=0.008], systolic blood pressure (SBP) [WMD = -9.50, 95% CI (-14.64, -4.37), P=0.000], diastolic blood pressure (DBP) [WMD = -4.588, 95% CI (-6.036, -3.140), P=0.000], cystatin-C (Cys-c) [WMD = -0.854, 95% CI (-0.99, -0.72), P=0.000], blood urea nitrogen (BUN) [WMD = -4.155, 95% CI (-6.152, -2.157), P=0.000]. Conclusion: The combination of HQI and antihypertensive drugs is more efficient in improving the related indexes of patients with hypertensive nephropathy than using antihypertensive drugs alone, and a moderate dose of HQI (no more than 30ml) may benefit more. However, the quality of the methodology is low and the number of samples is small, the results need to be confirmed by more stringent randomized controlled trials. Keywords: Hypertensive Nephropathy, Astragalus membranaceus (Fisch.) Bunge, Huangqi injection, Systematic review, Meta-analysis